Towards Sustainable Development: Formulating SDGs-Based Village RPJM in Bandung Village, Pandeglang: Menuju Pembangunan Berkelanjutan: Penyusunan RPJM Desa Berbasis SDGs di Desa Bandung, Pandeglang - Taufik Raharjo; Yuniato Hadiwibowo; Tanda Setiya; Nur Aisyah Kustiani (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
The purpose of this community service activity (PKM) is to assist in preparing the Village Medium-Term Development Plan (RPJM Desa) based on the SDGs of Bandung Village, Pandeglang. To achieve optimal results, this PKM activity is carried out in three stages, namely planning, implementation, and evaluation. The planning stage uses the Focus Group Discussion (FGD) approach with partners, to identify targets, objectives, expected outputs, and activity implementation schedules by calculating the use of appropriate resources, preparing implementation schedules, and designing other actions needed to achieve goals, including the division of tasks between the community service and partners. In the planning, the PKM implementation method is determined using a mentoring approach to the Bandung Village government. Mentoring is carried out by inviting several parties, from village officials to community leaders to prepare a Village Development roadmap based on the Village SDGs first. Evaluation is the last activity of this PKM. In the evaluation, it was found that the village government did not have complete data to be used in preparing the Village RPJM or the Village Development roadmap based on the SDGs. So the team had difficulty compiling the RPJM files and Village Development Roadmap. One solution is the need to input the lack of SDGs data in the Village SDGs application owned by the Ministry of Villages, Disadvantaged Regions, and Transmigration. However, until the end of this community service activity, the Village Government had not finished inputting the data in question, because of other activities such as preparing the Bandung village tourist location which will be opened at the end of 2023.